The Proposal for a Common European Sales Law And the Convention on the International Sale of Goods: Friends or Foes? - Calomme, Caroline (Europeanisation of Private Law, 2013)
This essay examines the relationship between the proposal for a Common European Sales Law and the Convention on the International Sale of Goods in B2B transactions and its future outcome on the law applicable to international commercial transactions: friends or foes? In order to do so, the analysis is comprised of six elements. The first section asks what threat the legal relationship between the two instruments poses. The second section evaluates how and to which extent business behaviour plays a role in the reliance on optional instruments. The next section inspects the level of achievement of the CISG from a diplomatic, legal and business perspective. Subsequently, the consequences of the European instrument on the legal environment are explored. Next, a series of examples illustrate whether the relationship between the two instruments is one of competition or of cooperation. Lastly, the future prospects for both instruments are looked at. In the end of this research, it is submitted that the CISG will enhance the chances of success of the CESL in the long term even though it is likely to affect its popularity for commercial transactions in the short term. Reversely, the CESL will pose a threat to the CISG in the beginning but it will progressively encourage the modernisation of international trade law instruments.